PERAN AKHLAK, KESEIMBANGAN JIWA, DAN CONDITIONING PESANTREN DALAM PEMBENTUKAN RESILIENSI SANTRI DI PONDOK PESANTREN DARUSSALAM BLOKAGUNG - Arif, Ahmad Syamsul Muarif (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2025)
This study addresses the role of morals, mental balance, and Islamic boarding school conditioning in fostering resilience in students at the Darussalam Blokagung Islamic Boarding School. A strong psychological state and character are essential for students to be able to face various life pressures and educational challenges in the Islamic boarding school environment. The purpose of this study is to comprehensively examine how these three aspects contribute to fostering mental resilience in students. The research method uses a qualitative phenomenological approach, involving students, caregivers, and Islamic boarding school educators. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using systematic data reduction, presentation, and verification techniques to ensure the validity of the findings. The results show that morals serve as a moral foundation that strengthens students' character, mental balance obtained from spiritual practices and emotional management helps maintain calm and focus, and Islamic boarding school conditioning, in the form of disciplined routines, forms positive habits that strengthen mental resilience. These three aspects synergistically form a solid and sustainable resilience for students at the Islamic boarding school.